Prevalence of Depression in Substance Use Disorder Patients in Rehabilitation Centers in Pokhara (Med Phoenix, 2025)
Introduction: The objective of the study is to find out prevalence of depression among substance use disorder patients in rehabilitation centres. It aims to determine the relationship among various drug abusing patterns, prevalence of depression with substance use disorder and severity of depression with duration and frequency of substance abused.Materials and Methods: The study was done in 3 rehabilitation centres at Pokhara, namely Richmond, Gateway and Helping hands rehabilitation centres. Ethical clearance was approved from Institutional Review committee (IRC) of Gandaki Medical College and Research Centre. One on one interview was taken using self-designed semi structured questionnaire to obtain information about socio-demography, types, duration and frequency of substance abused. Hamilton Depression Rating Scale was used for the rating of depression.Result: All 110 respondents were men with mean age of 26.57 ±8 years. The prevalence of depression in SUD patients was 38.2%, among whom 69% has mild depression and 31% has moderate level of depression. The link between depression and duration of substance abuse was found to be statistically significant (p